NEW PREDICTIVE PROFILES IN PLASMA FOR CARDIOVASCULAR RISK STRATIFICATION IN ASYMPTOMATIC INDIVIDUALS. (June 2018) - Baldan-Martin, M.; Lopez, J.A.; Corbacho-Alonso, N.; Martinez, P.J.; Rodriguez-Sanchez, E.; Calvo, E.; Alvarez-Llamas, G.; Ruiz-Hurtado, G.; Ruilope, L.M.; Barderas, M.G.
Abstract : Objective: The evaluation of cardiovascular (CV) risk is based on equations derived from epidemiological data useful in individuals who have advanced beyond the limits of middle age, such as the Framingham and SCORE risk assessments. On the other hand, the LifetimeRisk calculator (QRisk®), estimates CV risk throughout a subjects' lifetime, allowing those requiring a more aggressive and earlier intervention to be identified and offered protection from the consequences of CV and renal disease. The search for molecular profiles in asymptomatic individuals in middle age that allow a correct stratification of CV risk would be of great interest to adopt preventive therapeutic measures in individuals at high CV risk. Design and method: To improve the selection of subjects susceptible to intervention with aged between 30–50 years, we have employed a multiple proteomic strategy to search for new markers of early CV disease or reported CV events and to evaluate their relationship with LifetimeRisk. Blood samples from 71 patients were classified into 3 groups according to their CV risk (healthy controls, subjects with CV risk factors and patients with a previously reported CV event) and they were analyzed using a high through quantitative proteomics approach. Results: This strategy allowed three different proteomic signatures to be defined, two of which were related to CV stratification and the third one involved markers of organ damage. Conclusions: These protein profiles could serve as new markers for the early detection of asymptomatic individuals in middle age that would be expected to have an elevated LifetimeRisk of CV disease.